2019
DOI: 10.1177/1354816619863266
|View full text |Cite
|
Sign up to set email alerts
|

Tourism and poverty reduction: Empirical evidence from China

Abstract: This study empirically examines whether tourism affects poverty reduction based on the panel data of Chinese provinces for the period from 1999 to 2014. Using more comprehensive Foster–Greer–Thorbecke index to decompose poverty into three indices, namely, headcount ratio, poverty gap, and poverty severity, we investigate the relationship between tourism and poverty indices within a single framework. The empirical analysis indicates that tourism has a positive effect on poverty reduction and the concomitant ine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
67
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 38 publications
(49 reference statements)
7
67
0
2
Order By: Relevance
“…Consequently, the research with respect to pro-poor tourism has received increasing attention from many scholars in the academic circle [4]. However, there is a dispute about the effectiveness of pro-poor tourism [9]. Hence, it is necessary to examine the impacts of tourism on poverty alleviation.…”
Section: The Effect Of Tourism On Poverty Alleviationmentioning
confidence: 99%
See 2 more Smart Citations
“…Consequently, the research with respect to pro-poor tourism has received increasing attention from many scholars in the academic circle [4]. However, there is a dispute about the effectiveness of pro-poor tourism [9]. Hence, it is necessary to examine the impacts of tourism on poverty alleviation.…”
Section: The Effect Of Tourism On Poverty Alleviationmentioning
confidence: 99%
“…For example, Deller [10] demonstrated that tourism and recreation played a small role in reducing the poverty rate in the USA. On the contrary, Zhao and Xia [9] found that tourism development could contribute to poverty rate alleviation based on the panel data of Chinese provinces. Notably, the above two scholars conducted analysis from the macroscale.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…Scant studies related to BRICS nations have typically been country-based, with a significant gap emerging in empirical evidence of the tourismpoverty alleviation nexus explicitly based on the group of nations. In the case of China, a Generalized Method of Moments (GMMs) estimation on panel data (1999-2014) from Chinese provinces found that tourism has a positive effect on poverty alleviation in the country (Zhao & Xia, 2020). While, in the case of South Africa, Saayman et al (2012) applied a general equilibrium model and found that tourism inflows in the short-term would have to increase by at least 10% to result in a minimally significant benefit to the poorest households in South Africa.…”
Section: Tourism and Poverty Alleviation In The Bricsmentioning
confidence: 99%
“…Contemporary studies (Kim et al, 2016;Vanegas et al, 2015;Zhao & Ritchie, 2007;Zhao & Xia, 2020) have bemoaned the lack of more meaningful academic inquiry into the tourism-poverty alleviation nexus. To a larger extent, preceding empirical studies related to the role of tourism in the alleviation of poverty have also been critiqued for being sporadic and lacking the sufficient depth to comprehensively interrogate the tourism-poverty alleviation nexus, thus contributing to the lack of consensus and the existence of gaps within the extent of the tourism literature (Mitchell & Ashley, 2010;Saayman, Rossouw & Krugell, 2012;Zhao & Xia, 2020). Moreso, the extent of the literature is critiqued for being 'insufficient', generalist and overly descriptive in analyses based on predominantly single locations (Davidson & Sahli, 2015;Oviedo-García et al, 2019).…”
Section: Introductionmentioning
confidence: 99%